Editorial: The current Peruvian reality - El Director (2010)
The present number 10 of the !ECOS Journal offers the reader four studies that examine various problems of economic growth and one on the recent municipal elections, thus reflecting the interest of the academic community in two key aspects of the current Peruvian reality, since there is no doubt that economic growth presents restrictions that must be overcome, and on the other hand, the construction of a society of citizens makes it necessary to examine the circumstances of our electoral processes.